Classical Mythology and Children's Literature... An Alphabetical Odyssey - Hale, Elizabeth (Our mythical childhood, 2022)
Hale and Riverlea form the core of the Our Mythical Childhood project's Australasian team, and Classical Mythology and Children's Literature... An Alphabetical Odyssey incorporates reflection on children's literature from around the English-speaking world (and beyond), revealing the sheer volume and scope of a creative field that brings together ancient and modern for our youngest readers, connecting the past and the present, and inspiring the literary odysseys of the future.